2022
DOI: 10.3390/nano12071098
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived Ultrathin Cobalt Molybdenum Phosphide Nanosheets for Efficient Electrochemical Overall Water Splitting

Abstract: The development of high-performance and cost-effective earth-abundant transition metal-based electrocatalysts is of major interest for several key energy technologies, including water splitting. Herein, we report the synthesis of ultrathin CoMoP nanosheets through a simple ion etching and phosphorization method. The obtained catalyst exhibits outstanding electrocatalytic activity and stability towards oxygen and hydrogen evolution reactions (OER and HER), with overpotentials down to 273 and 89 mV at 10 mA cm−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The HER performance was evaluated using 1.0 M KOH electrolyte in a conventional three-electrode system and compared with Mo-CoP, CoP, and commercial Pt/C catalysts. [123] The results revealed that relatively lower HER overpotential of 89 mV at a current density of 10 mA cm À 2 was achieved for MOF-derived MoCoP nanosheets, which is slightly above that of Pt/C (42 mV) and well below that of Mo-CoP (154 mV), CoP (165 mV). In addition, the estimated Tafel slope of MOFderived MoCoP nanosheets (69.7 mV dec À 1 ) was also much lower than those of Mo-CoP (83.7 mV dec À 1 ), CoP (113.4 mV dec À 1 ) and close to that of Pt/C (56.1 mV dec À 1 ), which specify faster HER reaction kinetics by following Volmer-Heyrovsky mechanism (Figure 5a).…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 90%
See 1 more Smart Citation
“…The HER performance was evaluated using 1.0 M KOH electrolyte in a conventional three-electrode system and compared with Mo-CoP, CoP, and commercial Pt/C catalysts. [123] The results revealed that relatively lower HER overpotential of 89 mV at a current density of 10 mA cm À 2 was achieved for MOF-derived MoCoP nanosheets, which is slightly above that of Pt/C (42 mV) and well below that of Mo-CoP (154 mV), CoP (165 mV). In addition, the estimated Tafel slope of MOFderived MoCoP nanosheets (69.7 mV dec À 1 ) was also much lower than those of Mo-CoP (83.7 mV dec À 1 ), CoP (113.4 mV dec À 1 ) and close to that of Pt/C (56.1 mV dec À 1 ), which specify faster HER reaction kinetics by following Volmer-Heyrovsky mechanism (Figure 5a).…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 90%
“…[121] MOF-derived MoCoP, developed for HER by Wang et al, was also tested for its OER activities in 1.0 M KOH solutions. [123] In the OER test, an overpotential of only 273 mV at a current density 10 mA cm À 2 is observed and found to be relatively lower than that of Mo-CoP, CoP, and the benchmark OER catalyst RuO 2 . Apart from over potential, the estimated Tafel slope of 54.9 mV dec À 1 is found to be below that of Mo-CoP (60.4 mV dec À 1 ), CoP (71.5 dec À 1 ) and RuO 2 (86.4…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 92%
“…Large-surface-area-supports are needed to enable a high dispersion of the active phase. In this direction, the large surface area and tunable structure of metal–organic frameworks (MOFs) offer an ideal architecture to support catalytic active centers. Moreover, the metal nodes and aromatic linkers of MOFs can modify electronic energy levels through synergistic interaction between the different elements and π–π forces, thereby potentially enhancing the stability and activity of the active centers. Besides dispersing the active phase, supports play a strong role in binding the reactant molecule or its intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, many low-cost and highly-efficient electrocatalysts have been designed and prepared to replace noble metal catalysts for HER. Among them, transition-metal (Co, Ni, Mo, Cu, Fe) compounds, such as transition-metal oxides, sulfides, selenide, carbides, , phosphates, and nitrides, are demonstrated to be the most promising alternative electrocatalysts. At present, the biggest challenge of hydrogen production from electrolytic water is to find a suitable catalyst with low overpotential, ultrahigh current density, and long-term durability. , It has been found that nitrogen atom has a small radius and tends to occupy the interstitial sites in the original close-packed lattice of metal atoms when forming nitrides.…”
Section: Introductionmentioning
confidence: 99%